UX-MAPPER: An automated approach to analyze app store reviews with a focus on UX - Walter T. Nakamura; Edson C. C. de Oliveira; Elaine H. T. de Oliveira; Tayana Conte (Journal on Interactive Systems)
The mobile app market has increased substantially in the past decades, and the myriad options in the app stores have made users less tolerant of low-quality apps. In this competitive scenario, User eXperience (UX) has emerged as an essential factor in standing out from competitors. By understanding what factors affect UX, practitioners could focus on factors that lead to positive UX while mitigating those that affect UX negatively. In this context, app store reviews emerged as a valuable resource for investigating these influential factors. However, analyzing millions of reviews can be costly and time-consuming. This article introduces UX-MAPPER, a tool designed to analyze app store reviews and assist practitioners in pinpointing factors that impact UX. We applied the Design Science Research method to develop UX-MAPPER iteratively and rooted in a robust theoretical background. We performed exploratory studies to investigate the problem, a systematic mapping study to identify UX-affecting factors, and an empirical study to ascertain practitioners’ relevance and acceptance of UX-MAPPER. In general, the participants recognized the relevance and utility of UX-MAPPER in enhancing the quality of existing apps and exploring reviews of competing apps to identify user preferences, requests, and critiques regarding functionalities and features. However, the output quality requires refinement to better convey the benefits of the results, especially for practitioners with prior experience with automated approaches. From the participants’ feedback, we defined a set of suggestions to extract more useful features, which can contribute to future studies involving user review analysis. Based on the results of this research, we present the contributions to the area of HCI and possible developments for future research.